Ramona T. Mercer: Maternal Role Attainment-Becoming A Mother - Chairil Anwar; Irna Nursanti (STIKes Ibnu Sina Ajibarang, 2024)
Ramona T. Mercer began her medical career in 1950, when she received a Diploma from St. Mary's. Margaret's School of Nursing in Montgomery Alabama. He graduated with LL.Hill honors for his scholastic achievements. She went back to school in 1960 after working as an abortion officer, she received the maternal child health nurse of the year award from the national macro and primary foundation and the american nurses association, on various maternal child health proatices. Awards for research conducted were the America Societytes Psychoprophylaxis in Obstetrics (ASPO) / Lamaze National Research Award in 1987, The Honored, Researched Lecture Award, Western Institute of Nursing in 1958 and from the America Nurse Foundation Distinguehed Contribution of Nursing Science Award in 1958. 1990. (Mercer curriculum vitae, 2000). Mercer has written several articles, editors and opinions. He also published 6 books and 6 book chapters. At the beginning of his research, Mercer focused on the behavior and needs of breastfeeding mothers, mothers with post-partum illnesses, mothers who gave birth to babies with disabilities and young mothers. Her first book Nursing care for parents at risk (1977) received the American journal of Nursing book of the year award in 1978. Her study of teenage mothers passing the first year of married life in 1979, Perspective on nurse health care, also received American Journal of Nursing Book of the Year award in 1980.